Effects of Seawater Recharge on the Formation of Geothermal Resources in Coastal Areas and Their Mechanisms: A Case Study of Xiamen City, Fujian Province, China - Liu, Chunlei; Li, Yasong; Cao, Shengwei; Wang, Wanli; Li, Jing (Frontiers in Earth Science, 2022)
The southeast coastal areas of China have abundant geothermal resources. Most especially, seawater-recharged geothermal systems in the coastal areas have large quantiles of recharge but suffer water salinization and low water temperature. Moreover, the geothermal water development in these areas may induce seawater intrusion. Understanding the genetic patterns of geothermal resources is significant for rational exploration and protection. This study analyzed the hydrochemical and environmental isotopic characteristics of geothermal water, groundwater, and surface water samples collected in the area with geothermal resources in Xiamen Province in the southeast coastal areas of China. Based on this, the recharge of geothermal water circulation and the genetic patterns of geothermal resources were revealed. The results of this study indicate that the geothermal water in mountainous areas and piedmonts in Xiamen is mainly recharged by rainfall infiltration. In contrast, the geothermal water in coastal areas in Xiamen is recharged by seawater mixing to different extents, as indicated by hydrochemical types, isotopic characteristics, and the C1-/Br- ratio of geothermal water. As revealed by the calculation results using the Cl− mixing model, 10 of 13 geothermal fields in Xiamen are recharged by seawater mixing, with a mixing ratio of up to 73.20% in the Pubian geothermal field. After being recharged by rainfall in the low mountainous areas, geothermal water migrates toward deep parts along NW-trending faults. Then, it converges with regional NE-trending deep faults to absorb heat conducted from deep parts to form deep geothermal reservoirs. The deep geothermal reservoirs were estimated to be 185–225°C using the silica-enthalpy mixing model. The geothermal water is mixed with cold water or seawater while rising along faults. The temperature of shallow geothermal reservoirs was estimated to be 71–145°C using SiO2 geothermometers.